Oral Health and Related Behavior of Children Aged 9–12 with Attention Deficit Hyperactivity Disorder in Tron District, Thailand - Khobkham, Duangruethai; Korwanich, Kanyarat; Korwanich, Narumanas (UI Scholars Hub, 2020)
Attention deficit hyperactivity disorder (ADHD) is a common biobehavioral childhood disorder that leads to significant behavioral problems that affect everyday life. Objective: This study aimed to compare oral health and oral health behaviors among children with and without ADHD. Methods: The study included 105 children aged 9–12 years with ADHD and 105 age-, gender-, and family income-matched children without ADHD. Clinical data as caries, periodontal health, and traumatic dental injuries were recorded by calibrated examiners. All parents of the children completed questionnaires about the oral health behaviors of their children by a single interview. Data were compared using Chi-square test, McNemar test, and Paired t-test at the significance level of 0.05. Results: The children with ADHD had significantly lower tooth brushing frequency and shorter tooth brushing duration compared with the children without ADHD. The two groups had equivalent dental trauma prevalence (1.9%). Compared with the children without ADHD, the children with ADHD had significantly more decayed, missing, and filled teeth (3.24±2.14 vs. 2.25±2.23). Therefore, 11.4% of the children in the ADHD group were caries free compared with the 30.5% in the non-ADHD group. The children with ADHD had 3.9 times the odds of prevalence dental caries than the children without ADHD. The children with ADHD had significantly higher Simplified Debris Index and Simplified Calculus Index values than the children without ADHD. Conclusion: Children with ADHD exhibited a higher prevalence of caries and periodontal problems than children without ADHD.